Benefits of Family and Social Relationships for Thai Parents Living with HIV - Rotheram-Borus, Mary Jane (2010)
Family and social relationships are important structural supports in Thailand that are likely to influence the health and mental health of persons living with HIV (PLH). Structural equation modeling examined these relationships among 409 PLH in two communities in Thailand. Latent variables were constructed for most outcomes and mediators, with adherence to antiretroviral (ARV) therapy, depression, and disclosure represented by single-item indicators. All models controlled for gender, age, and education. Disclosure was significantly and positively associated with ARV adherence, and to both family functioning and social support. Family functioning and social support were significantly related to the PLH’s self-perceptions of health and mental health, as well as being significantly correlated with each other. Better family functioning was significantly associated with better quality of life, better perceived health, fewer symptoms of depression, and greater ARV adherence. Social support was significantly associated with better quality of life and fewer depressive symptoms. These results highlight the important role that an organized and structured family life and social support network can play in encouraging better health outcomes among PLH.